2016
DOI: 10.1017/s1751731115002827
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differences based on a beef terminal index are reflected in future phenotypic performance differences in commercial beef cattle

Abstract: The increased demand for animal-derived protein and energy for human consumption will have to be achieved through a combination of improved animal genetic merit and better management strategies. The objective of the present study was to quantify whether differences in genetic merit among animals materialised into phenotypic differences in commercial herds. Carcass phenotypes on 156 864 animals from 7301 finishing herds were used, which included carcass weight (kg), carcass conformation score (scale 1 to 15), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
53
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 28 publications
10
53
2
Order By: Relevance
“…The superior carcass metrics of the animals excelling in the terminal index in the present study have also previously been demonstrated by Connolly et al (2016) . Using a national database, Connolly et al (2016) reported that cattle in the very high genetic merit stratum for a terminal index had a 37.1 kg heavier carcass, a 1.98 units superior carcass conformation (scale 1 to 15) and a 1.33 units less carcass fat (scale 1 to 15), relative to cattle in the very low genetic merit stratum.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The superior carcass metrics of the animals excelling in the terminal index in the present study have also previously been demonstrated by Connolly et al (2016) . Using a national database, Connolly et al (2016) reported that cattle in the very high genetic merit stratum for a terminal index had a 37.1 kg heavier carcass, a 1.98 units superior carcass conformation (scale 1 to 15) and a 1.33 units less carcass fat (scale 1 to 15), relative to cattle in the very low genetic merit stratum.…”
Section: Discussionsupporting
confidence: 84%
“…The superior carcass metrics of the animals excelling in the terminal index in the present study have also previously been demonstrated by Connolly et al (2016) . Using a national database, Connolly et al (2016) reported that cattle in the very high genetic merit stratum for a terminal index had a 37.1 kg heavier carcass, a 1.98 units superior carcass conformation (scale 1 to 15) and a 1.33 units less carcass fat (scale 1 to 15), relative to cattle in the very low genetic merit stratum. The smaller differences between the very high and very low genetic merit strata reported in the present study, for the same index and the same traits, are likely due to the fact that the difference in terminal index value between adjacent terminal index strata in Connolly et al (2016) was approximately 17% greater than that in the present study (€51.30 vs. €43.72).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…It is possible, therefore, to use genetically superior (beef) bulls based on a terminal index (Connolly et al, 2016), which would improve the carcass characteristics of the resulting progeny (Clarke et al, 2009;Connolly et al, 2016) but could also achieve this without necessarily increasing calving dystocia (McHugh et al, 2014). Despite detecting a significant interaction between animal genetic merit and subsequent performance depending on whether or not the cattle originated from a dairy herd (bucket reared) or a beef herd (suckled until weaning), Connolly et al (2016) concluded that the biological significance of the interaction was minimal and that a beef terminal index functions equally well irrespective of the origin of the cattle. Hence, strategies do exist to lessen the effect of Jersey bloodline on beef merit while still protecting one of the main benefits of Jersey cows, which is their superior gross efficiency.…”
Section: Jerseymentioning
confidence: 99%